Enhancing the efficiency of polypyrrole-dodecylbenzene sulfonic acid in-tube solid-phase microextraction coating for analysis of nitrogen-containing pesticides in water environments - Ma, Rong; Yu, Shuangshuang; Li, Yafang; Lin, Yan; Ma, Xiaodong (Frontiers in Environmental Science, 2024)
With the widespread use of nitrogen-containing pesticides in agricultural production, their environmental residues have become a focal point of public health concern. This study developed a novel coating based on PPy-DBSA/IT-SPME aimed at enhancing the detection efficiency of polar nitrogen-containing pesticides. By optimizing the preparation conditions, including pyrrole concentration of 7.0 mol/L, DBSA concentration of 0.014 mol/L, oxidant concentration of 0.35 mol/L, and a coating cycle of 10 times, efficient adsorption of 19 different categories of polar nitrogen-containing pesticides was achieved. These pesticides encompass sulfonylureas, triazoles, diphenyl ether herbicides, benzoylurea insecticides, and substituted urea herbicides, with adsorption rates below 10.0%. Moreover, by integrating HPLC-MS/MS technology, this study established a green, efficient, simple, and cost-effective analytical method suitable for detecting polar nitrogen-containing pesticide residues in water matrices. The method exhibited an average recovery rate between 61.92% and 115.21%, RSD below 5.0%, and detection and quantification limits ranging from 0.012-0.524 μg/L and 0.127-5.243 μg/L, respectively, demonstrating good recovery and precision. This research provides an environmentally friendly, efficient, and user-friendly approach for detecting polar nitrogen-containing pesticide residues in water, with potential wide application in environmental monitoring and food safety.